Maternal Factors that Determining Birth Spacing Interval among a Sample of the Women at Child Bearing Age - Noaman, Aqeel Abbas (Diyala Journal of Medicine, 2019)
Background: Birth interval is the length of time between two successive live births. It might be affected with socio-economic factors related to mother as age, education and parity. Objectives: To determine the rate of birth spacing interval for a sample of women at the child bearing age and to find out any association between maternal factors and birth spacing interval. Subjects and methods: A cross-sectional study was conducted in Al- Takia PHC center by using special questionnaire from 15th September 2012 to 15th September 2013. Sample size was 184 women at child bearing age. Results: Out of 184 women at the child bearing age (60.33%) had birth interval less than two years, (68.5%) below 25 years had birth interval shorter than two years, (60%) and (32.9%) of women with birth spacing interval < 2 years and ≥ 2 years respectively were primary school graduates, (83.8%) and (74%) of the studied women with birth spacing interval < 2 years and ≥ 2 years respectively were housewives, (45.9%) of women with birth interval < 2 years had high parity ( ≥ 5 live births). Conclusions: All studied maternal factors were significantly associated with length of birth interval except mother's work status.